A internet e as novas tecnologias na relação de trabalho: teletrabalho / home office e a jornada de trabalho - Felippe, Gabriela de Carvalho (2019)
The evolution of technology has been deeply impacting many areas of science and, as a consequence, the Law, which ignited our interest in researching a new way of working called teleworking. As the studies around the theme went further, we noticed that the new wave of working remotely, and especially the advent of teleworking, as expected, reflected in changes in the means of production stemming from the elimination of borders and the process of globalization of economy. Despite the recent changes in legislation, we observed that there is a lack of understanding on the difference between the concepts of teleworking and home office, which prompted us to dedicate our research to the concept/difference even before diving into the question of the possibility or impossibility of controlling the workday and what mechanisms can be used to measure it. With this paper, we will demonstrate that the supervision of teleworkers is a challenge to Labor Law due to the nuance involved in the work done remotely along with the mitigation of the concept of subordination and the efforts to soften the Law. While studying the theme we also superficially approached the matter of Occupational Medicine and Workplace Safety, and in the final considerations we set out to make this paper thought-provoking, with the intention of coming up with inspecting mechanisms that don’t restrict the company but offer solutions that ensure the employee’s right to disconnect